Implementing a Participatory Human Rights-Based Research Methodology: The Unfitness to Plead Project. (22nd December 2019) - Arstein-Kerslake, Anna; Gooding, Piers; Mercer, Sarah; Raymond, Marlena; McSherry, Bernadette
Abstract: This article describes a novel action-research methodology that combines aspects of participatory methods and emancipatory principles into a human rights-based framework. The history of these different methods is discussed and the authors then explain how the methods can be combined to create a participatory human rights-based research methodology. This new methodology has the potential for high social impact, community inclusion, and scholarly output. The article also describes the implementation of the methodology on a project which analysed the human rights compliance of unfitness to plead laws in the Australian criminal justice system. This project developed a system of support persons within community legal centres across Australia in order to build an evidence-base for good practice in supporting people with cognitive disability who are charged with a crime. The new participatory human rights-based methodology was successful on this project and is replicable in future human rights research.